Advanced CFD-CSD coupling: Generalized, high performant, radial basis function based volume mesh deformation algorithm for structured, unstructured and overlapping meshes - Schuff, M.; Kranzinger, P.; Kessler, M.; Krämer, E. (My University, 2014)
Radial basis functions (RBF) are used for interpolation of moving 3D multigrid volume meshes based on their surface deformation. The method is independent of grid connectivity and can easily handle any structured, unstructured and overlapping mesh setup. For flexibility and reusability, an object oriented C++ library has been developed for easy integration into any flow solver. Furthermore, highly distributed computation is addressed. Since high resolution meshes contain way more surface points than accurate mesh deformation based on RBF interpolation needs, an efficient grid coarsening algorithm based on an octree has been implemented by which performance can be boosted considerably. Various setups using the new algorithm are presented. The method is applied to a typical dynamic aeroelastic problem – the fast-forward flight of a weakly coupled five bladed isolated rotor simulation. The validation was executed by comparing the resulting trim angles and loads with a formerly used algorithm.